2014
DOI: 10.1016/j.medici.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dyslipidemia in statin-treated patients in the Baltic states (Estonia, Latvia, and Lithuania): Results of the Dyslipidemia International Study (DYSIS)

Abstract: Our findings indicate many statin-treated patients in Estonia, Latvia, and Lithuania did not meet target lipid levels and had a very high risk of CVD. Combating other well-known CVD risk factors such as obesity and hypertension is vital to reduce the exceptionally high risk for CVD mortality seen in the Baltic nations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The Baltic States (Estonia, Latvia and Lithuania) appeared to be among the most profoundly CVD-affected countries within Europe with very high CV mortality rates compared to other countries in the EU [ 10 , 34 ]. It was explained by high prevalence of CV risk factors (dyslipidemia, obesity, diabetes and hypertension) that may relate to a larger proportion of poorer and older people, patients with lower education, as well as those outside social support networks, problems in doctor-patient relationship, inadequate dosing of drugs, unhealthy lifestyle [ 36 , 37 ]. Comorbidity of depression and/or anxiety with CVD as a possible explanation has not been sufficiently examined in the Baltic region.…”
Section: Introductionmentioning
confidence: 99%
“…The Baltic States (Estonia, Latvia and Lithuania) appeared to be among the most profoundly CVD-affected countries within Europe with very high CV mortality rates compared to other countries in the EU [ 10 , 34 ]. It was explained by high prevalence of CV risk factors (dyslipidemia, obesity, diabetes and hypertension) that may relate to a larger proportion of poorer and older people, patients with lower education, as well as those outside social support networks, problems in doctor-patient relationship, inadequate dosing of drugs, unhealthy lifestyle [ 36 , 37 ]. Comorbidity of depression and/or anxiety with CVD as a possible explanation has not been sufficiently examined in the Baltic region.…”
Section: Introductionmentioning
confidence: 99%
“…High-intensity statin utilization became more prominent only in recent years when a minor decline in mortality was observed. Furthermore, the Dyslipidemia International Study completed in Lithuania, Latvia, and Estonia revealed that many patients treated with statins did not meet the LDL-C and other lipid targets ( 24 ). Thus, 80.7% of all patients in the study had elevated LDL-C despite being on statin treatment, and in the very high CVD risk group, 86.5% of the patients did not attain their LDL-C goals.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not have any reason to believe that the use of other medications would differ significantly between epilepsy-positive and negative subgroups within one cohort. Also, as dyslipidemia is a common disorder among the adult population [ 43 ], we were unable to rule out the presence of undiagnosed cases among the EstBB participants. Conversely, there might be participants with dyslipidemia who use statins or other lipid-modifying agents and therefore have normal blood lipid levels.…”
Section: Discussionmentioning
confidence: 99%